2014
DOI: 10.1021/ic4031014
|View full text |Cite
|
Sign up to set email alerts
|

Copper Diamidocarbene Complexes: Characterization of Monomeric to Tetrameric Species

Abstract: Treatment of CuCl with 1 equiv of the in situ prepared N-mesityl-substituted diamidocarbene 6-MesDAC produced a mixture of the dimeric and trimeric copper complexes [(6-MesDAC)CuCl]2 (1) and [(6-MesDAC)2(CuCl)3] (2). Combining CuCl with isolated, free 6-MesDAC in 1:1 and 3:2 ratios gave just 1 and 2, respectively, while increasing the ratio to >5:1 allowed the isolation of small amounts of the tetrameric copper complex [(6-MesDAC)2(CuCl)4] (3). Efforts to bring about metathesis reactions of 1 with MOtBu (M = L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 86 publications
4
20
0
Order By: Relevance
“…However,when LiAlH 4 addition was carried out at 178 K, the Cu-H product (2) proved to be stable.DOSY measurements showed that it was dimeric (Scheme 2). [7,8] Thec omplex exhibited al ow fre-quencyC u-H resonance at d = 0.96 ppm, in good agreement with the shifts recently reported for [(6/7Dipp)Cu(m-H)] 2 species. [3d,9] However,w hereas [(6/7Dipp)Cu(m-H)] 2 prove stable for days at 298 K, 2 was stable only below 209 K. Above this temperature,t he 1 HNMR resonances began to broaden and at 255 Ks ignals for 3 were present.…”
supporting
confidence: 87%
“…However,when LiAlH 4 addition was carried out at 178 K, the Cu-H product (2) proved to be stable.DOSY measurements showed that it was dimeric (Scheme 2). [7,8] Thec omplex exhibited al ow fre-quencyC u-H resonance at d = 0.96 ppm, in good agreement with the shifts recently reported for [(6/7Dipp)Cu(m-H)] 2 species. [3d,9] However,w hereas [(6/7Dipp)Cu(m-H)] 2 prove stable for days at 298 K, 2 was stable only below 209 K. Above this temperature,t he 1 HNMR resonances began to broaden and at 255 Ks ignals for 3 were present.…”
supporting
confidence: 87%
“…compared to that of 2 and (DAC)CuCl (1.886(2) Å) 48 are consistent with added steric repulsion arising from the presence of a second carbene ligand or a 2,6-disubstituted aryl group.…”
Section: Synthesis and X-ray Structuressupporting
confidence: 58%
“…21,23,[38][39][40][41][42][43] In this work, we have investigated four linear diamidocarbene Cu(I) complexes (Figure 1), the previously reported [(DAC)2Cu][BF4] (1) 30 and (DAC)Cu(2,4,6-Me3C6H2) (4), 44 to their diamino counterparts. [45][46][47][48] We show that the bis(diamidocarbene) complex 1 exhibits high photoluminescence quantum efficiency in CH2Cl2 solution and its phosphorescence is only weakly quenched under aerobic conditions, which differs from most other luminescent Cu(I) complexes. [7][8][9] (Figure 1).…”
Section: Introductionmentioning
confidence: 87%
“…The X-ray structures of the two compounds are shown in Figure 1a nd confirmedt he anticipated two-coordinate geome-tries. Both the CuÀC NHC (1:1 .852(3) ; 2:1 .874(2) ) and CuÀO distances (1:1 .793(2) ; 2:1 .8016 (15) ) werev ery close to the values in the five-membered ring NHC derivatives [(IPr)CuO-tBu] [6] and [(IPr/SIPr)CuOEt]. [8a, b] Degradation of 1i ns olution…”
Section: Resultsmentioning
confidence: 94%
“…These diamidocarbenes, or DACs, exhibit ambiphilic properties; [12] they are nucleophilic enought oc oordinate to metal centres, [12,13] but can also behave as electrophilesi nb ringinga bout small molecule activation. [13a, 14] In previousw ork, [15] we described what provedt ob e ultimately fruitless attempts to prepare the diamidocarbene alkoxide complex [(6-MesDAC)CuOtBu] (1)t hrough the addition of MOtBu (M = Li, Na, K) to Cu(m-Cl)] 2 .I n contrast to Na and K tert-butoxide, which gave intractable mixtures, LiOtBu reactedc leanly,b ut only to bring about partial salt metathesis to give the ate complex [(6-MesDAC)CuCl· LiOtBu·2THF].W en ow report alternative strategies that have allowed the successful synthesis of 1,t ogether with the diaminocarbene analogue[ (6-Mes)CuOtBu] (2). Use of these two electronically quite different complexes as precursors to the corresponding [(6-NHC)CuH] speciesr evealed that both the 6-MesDAC and, more surprisingly,t he less electrophilic 6-Mes ligand undergo migratory insertion reactions with the CuÀH groups.T his process is too rapid to allow detection of [(6-Mes-DAC)CuH],b ut slower in the case of the 6-Mes complex, allowing it to be intercepted and employed in both stoichiometric and catalytic transformations.…”
Section: Introductionmentioning
confidence: 99%